Horizontal Shear Strength at the Interface of the Concrete Beams Cast in Two Time Stages - Abushaaban, Hatem Ady (2020)
Composite concrete is a method of construction that uses both precast and cast in situ concrete to produce a structural element. In framing big slabs areas, the use of precast slabs and beams is being an economical way of construction. The best procedure is to employ beams of inverted T section, which bottom flange will act as a ledge to seat the precast slab. Topping concrete slab is then cast on top of the precast slabs and beams. It is cleaner and safer than the full cast in place construction. This kind of construction which is cast in two stages at different times reduces the quantities of formworks at site and reduces the back propping which in some cases is required to be extended below to multiple levels according to the expected construction loading. Accordingly, more clear spaces for lower levels will be available so that other site activities can be accomplished to complete the job faster with less building materials and reduced risk levels. The bond strength between the precast concrete part and the cast in place part is essential to provide the monolithic behavior for the composite concrete members. The integrated monolithic behavior is achieved only if all forces including the horizontal shear are fully transferred at the interface. From the structural normal practice, the word “interface” means the plane between two different materials; such as concrete to steel or concrete to concrete that is cast in stages at different ages. This interface which is studied in this dissertation is that the plane between the precast and the cast in situ parts of the composite concrete beams. The rough surface of the precast beam part, aggregate interlock, concrete strength and the steel bars crossing the interface between the cast in place and precast parts are the main factors that affect the horizontal shear strength of the that interface. The international design codes propose semi empirical equations to determine the horizontal shear strength considering adhesion, friction caused by normal stress and friction caused by interface steel rebar clamping stress. Usually the experimental tests are done on series of specimens of small size and in some other cases, are done on small sized composite beams of short span that can be accommodated in a concrete testing facility. The small specimens testing somehow reduced the level of reliability of the results. Accordingly, there is a considerable difference in the proposed interface shear strength limits between the different structural design codes. This dissertation presents a study of four composite beams with different sections, properties and reinforcement that were experimented for shear friction in a previous research. The beams are modeled using a 3D finite element software. A shear friction design hand calculation is provided as well using the provisions and equations proposed by the code of practice. The dissertation provides a comparison between simplified code approach, 3D finite element model and results from the experimental work published by Anil Patnaik at 1992.